The Doctor she should resist - Ruttan, Amy (Harlequin medical romance ;, 2022)
"The last thing midwife Hazel is looking for is a relationship. So, why is she so drawn to Dr Caleb? Especially when he's from the rival hospital that delayed the opening of her birthing centre. Enigmatic Caleb knows just how to push all of her buttons...for all their differences sparks of chemistry soon start to fly! But with Hazel's heart already damaged, can she believe that Caleb will be the one to heal it?" -- Back cover.